2014
DOI: 10.1038/ncomms4903
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted terminally differentiated induced pluripotent stem cells are accepted by immune mechanisms similar to self-tolerance

Abstract: The exact nature of the immune response elicited by autologous induced pluripotent stem cell (iPSC) progeny is still not well understood. Here we show in murine models that autologous iPSC-derived endothelial cells (iECs) elicit an immune response that resembles the one against a comparable somatic cell, the aortic endothelial cell (AEC). These cells exhibit long-term survival in vivo and prompt a tolerogenic contexture of intra-graft characterized by elevated IL-10 expression. In contrast, undifferentiated iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 46 publications
(51 reference statements)
5
135
0
1
Order By: Relevance
“…NSCs isolated from syngeneic C57BL/6 mice and allogeneic ICR mice were transplanted into EAE mice, and used as positive and negative controls respectively. (Araki et al, 2013;de Almeida et al, 2014). To investigate whether NSCs derived from iPSCs can elicit immune rejection responses and thus affect their clinical applications, T cell stimulation assays were performed.…”
Section: Immunogenicity Analysis Of Ipsc-nscsmentioning
confidence: 99%
“…NSCs isolated from syngeneic C57BL/6 mice and allogeneic ICR mice were transplanted into EAE mice, and used as positive and negative controls respectively. (Araki et al, 2013;de Almeida et al, 2014). To investigate whether NSCs derived from iPSCs can elicit immune rejection responses and thus affect their clinical applications, T cell stimulation assays were performed.…”
Section: Immunogenicity Analysis Of Ipsc-nscsmentioning
confidence: 99%
“…By contrast, autologous iPSCs may avoid the costs and side effects associated with lifelong immunosuppression required for allogeneic cell transplantation (16). Despite some controversy over the immunogenicity of undifferentiated iPSCs (40), recent work has demonstrated that the differentiation of iPSCs results in the loss of immunogenicity (41). Pending further validation, this is a potentially important finding, because it could lead to induction of tolerance similar to the tolerance elicited by a corresponding self-somatic cell.…”
Section: Immunogenicity Studiesmentioning
confidence: 98%
“…Subsequently, experiments with isogenic transplantation of mouse iPSCs revealed the successful engraftment of iPSCderived tissue without immunosuppressive treatment and verified the advantages of using auto-transplantation of iPSCs for avoiding immunosuppressive treatment [112,113] . However, a recent study demonstrated immune rejection upon transplanting autologous undifferentiated mouse iPSCs in vivo, and rejection was imperceptible upon transplanting autologous terminally differentiated mouse iPSCs [114] . Although this report supports the presence of immunogenicity in undifferentiated iPSCs [91] and conflicts with the successful autologous engraftment of undifferentiated iPSCs in other reports [93,94] , it supports the advantages of using auto-transplantation of iPSCderived terminally differentiated cells for avoiding immunosuppressive treatment.…”
Section: Transplantation Of Ipscsmentioning
confidence: 99%